Anatomy of a Con Artist: The 14 Red Flags to Spot Scammers, Grifters, and Thieves - Walton, Johnathan (New York, NY : Rodale, 2025)
"Con artists are everywhere-your new boyfriend or girlfriend, your new neighbor or coworker, your new friend-and they don't outsmart you; they out-feel you to get their hands on your money. In Anatomy of a Con Artist, Walton lays out "the tells" based on hundreds of real-life cases he's investigated, including: Red Flag #1-A Stranger Offering Help: Someone new and overly helpful insinuates themselves into your life. Red Flag #3-Drama, Drama, Drama: Constant dramatic "emergencies" to pull you in. Red Flag #8-Beak Wetting: Faux generosity-gifts, money, or favors to bring your guard down. After being scammed out of nearly $100,000 by a devious con artist, Walton was turned away by police. Infuriated and armed with the investigative skills he'd gained from years as a TV reporter, Walton launched his own investigation and built a compelling criminal case authorities could not ignore. Walton got his con artist charged, prosecuted, and convicted, then devoted his life to helping other victims do the same. This book packs in all he has learned. Some con artists scheme for money, some for attention, some just for the thrill of lying. And if you think it can't happen to you, then you are exactly the kind of "mark" a professional con artist is looking for. With this insightful guide in your hands, you are far less likely to get conned and far more likely to spot these nefarious manipulators from a mile away-and cross the street when you see them coming"-- Provided by publisher.
Includes index.
new book 2025 summer.
Keywords: Walton, Johnathan; Swindlers and swindling; TRUE CRIME / Con Artists, Hoaxes & Deceptions; Personal Safety & Self-Defense; Safety & Security; SELF-HELP; TRUE CRIME / General